Proof: Substitution in the Middle
Let's prove the following theorem:
if a + b = c, then ((x + a) + b) + y = (x + c) + y
Proof:
Given
1 | a + b = c |
---|
# | Claim | Reason |
---|---|---|
1 | x + (a + b) = x + c | if a + b = c, then x + (a + b) = x + c |
2 | (x + a) + b = x + (a + b) | (x + a) + b = x + (a + b) |
3 | (x + a) + b = x + c | if (x + a) + b = x + (a + b) and x + (a + b) = x + c, then (x + a) + b = x + c |
4 | ((x + a) + b) + y = (x + c) + y | if (x + a) + b = x + c, then ((x + a) + b) + y = (x + c) + y |
Comments
Please log in to add comments